2018
DOI: 10.1002/uog.19068
|View full text |Cite
|
Sign up to set email alerts
|

Outcome reporting across randomized trials and observational studies evaluating treatments for twin–twin transfusion syndrome: systematic review

Abstract: Studies evaluating treatments for TTTS have often neglected to report clinically important outcomes, especially neonatal morbidity outcomes, and most are not designed for long-term follow-up. The development of a core outcome set could help standardize outcome collection and reporting in TTTS studies. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 134 publications
1
40
0
2
Order By: Relevance
“…A protocol including explicitly defined objectives, study selection criteria, and data extraction methods was developed. The protocol was informed by other evaluations in pre‐eclampsia, endometriosis, obstetrics, and urogynecology . Ethical approval for this study was not required.…”
Section: Methodsmentioning
confidence: 99%
“…A protocol including explicitly defined objectives, study selection criteria, and data extraction methods was developed. The protocol was informed by other evaluations in pre‐eclampsia, endometriosis, obstetrics, and urogynecology . Ethical approval for this study was not required.…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of fetoscopic laser treatment for TTTS has benefited women and their babies worldwide. Despite over 20 years of research on TTTS, the recent systematic review on outcome reporting across studies evaluating treatments for TTTS identified only six randomized controlled trials on this subject. Evidence remains scarce relating to the optimal surgical approach, prognostic factors of outcome before and after laser treatment, and use of laser in Stage‐I TTTS, triplet pregnancy or TTTS co‐existent with selective fetal growth restriction (sFGR).…”
Section: Characteristics Of 39 Studies Evaluating Interventions For Smentioning
confidence: 99%
“…We investigated systematically the variation in outcome reporting across studies evaluating interventions for sFGR in monochorionic diamniotic twin pregnancies, according to the methodology reported in the linked systematic review of outcome reporting in TTTS and the Cochrane Collaboration handbook, COMET initiative handbook and other core outcome sets in development. MEDLINE, EMBASE, CINAHL, http://clinicaltrials.gov and The Cochrane Library databases were searched electronically using a comprehensive search strategy (Appendix S1).…”
Section: Characteristics Of 39 Studies Evaluating Interventions For Smentioning
confidence: 99%
See 1 more Smart Citation
“…Although previously the variation in outcome reporting has been investigated and confirmed in several areas relevant to obstetrics and gynaecology, no evaluation has been undertaken in childbirth trauma research …”
Section: Introductionmentioning
confidence: 99%